PENGARUH MODEL PEMBELAJARAN ALGORITMIK-HEURISTIK DAN GAYA BELAJAR TERHADAP HASIL BELAJAR MATA KULIAH PERKEMBANGAN INDIVIDU PADA MAHASISWA PROGDI BK FKIP UNISRI SURAKARTA - Fadjeri, Soewalni Soekirno (UNIVERSITAS SLAMET RIYADI, 2014)
The research aims at determining the effect of the learning model and student learning styles. Learning model consists of : (1) Heuristic learning model and (2) Algorithmic learning model. Student learning styles consist of : (1) Learning Styles and Field Independence (2) Learning Styles Field dependence. Student population that is affordable Guidance Counseling (BK) semester IV by 74 people. The sample consisted of 20 students with learning styles field independence and 20 students with learning style field dependence. Data collection techniques using test techniques for data treatment outcome study after learning models. A survey technique used to obtain data about learning styles. This experimental study using 2 x 2 factorial analysis (ANOVA) . The results also show that : (1) The study of heuristic learning model higher than algorithmic learning model on student with learning styles of field independence (Fo = 5.20 > 4.17 ft). (2) The Study of the learning style of field independence of higher learning style of field dependence (Fo = 5.55 > 4.17 ft). (3) An interction between learning style model of learning and student learning outcomes ( Fo = 9.36 > 4.17 ft) on the development of individual subyects. Conclution accurate heuristic model used student learning with the learning styles field independence and algorithmic learning model is suitable for students with learning style field dependence. Let more attention to the learning process and student learning styles learning model variations. Â Keywords: algorithmic-heuristic learning models, learning style field dependence, field independence